Everything is under control: Buber’s critique of Heidegger’s magic - Herskowitz, D (Springer, 2019)
As part of a religiously-oriented analysis, Martin Buber associates Martin Heidegger’s later philosophy with magic. The present article is dedicated to explicating and evaluating this association. It does so, first, by fleshing out how Buber comes to depict Heidegger as an advocate of magic. Then, by examining other appearances of the category of magic in the wider context of Buber’s dialogical oeuvre, it demonstrates that what he has in mind when he invokes this category is a specific manner of human appeal to the divine marked by manipulation, utility and control. Finally, it evaluates the affiliation of Heidegger with magic: first, by comparing the metaphysical presuppositions undergirding the logic of magic—specifically the conceptions of, and interrelations between, ‘language’ and ‘being’—with Heidegger’s views, and second, by judging whether the claim that Heidegger promotes manipulative, utilitarian, and power-laden attitudes can be justified in light of his analysis of ‘technology’. The article ultimately argues that Buber misattributes magic to Heidegger, and that this misattribution better reflects the theoretical framework through which Buber justifies his dialogical position than an apt assessment of Heidegger’s thought.